Unique reporter-based sensor platforms to monitor signalling in cells. - Meesbah Jiwaji; Rónán Daly; Abdullah Gibriel; Gráinne Barkess; Pauline McLean; Jingli Yang; Kshama Pansare; Sarah Cumming; Alisha McLauchlan; Piotr J Kamola; Musab S Bhutta; Adam G West; et al. (PLoS ONE)
Introduction In recent years much progress has been made in the development of tools for systems biology to study the levels of mRNA and protein, and their interactions within cells. However, few multiplexed methodologies are available to study cell signalling directly at the transcription factor level. Methods Here we describe a sensitive, plasmid-based RNA reporter methodology to study transcription factor activation in mammalian cells, and apply this technology to profiling 60 transcription factors in parallel. The methodology uses two robust and easily accessible detection platforms; quantitative real-time PCR for quantitative analysis and DNA microarrays for parallel, higher throughput analysis. Findings We test the specificity of the detection platforms with ten inducers and independently validate the transcription factor activation. Conclusions We report a methodology for the multiplexed study of transcription factor activation in mammalian cells that is direct and not theoretically limited by the number of available reporters.